TALENT AND TALENT MANAGEMENT PRACTICESM: AN HRM PERSPECTIVE - Kaul, A.K. (International Journal of Psychosocial Rehabilitation, 2021)
Employees in any organization are quintessentially critical for the sustenance, growth and development of any forward looking organization. Vital Human capital plays an extremely important role in realizing the strategic goals and objectives. In an age where war of Talent is fiercely rampant, employees with requisite talent are scarce and definitely in short supply as compared to the ongoing and ever burgeoning demand. This brings, in the new Talent Age, effective Talent Management Practices or TMP to the fore with basic function of not only Acquisition of Talented employees but also developing, motivating and maintaining them in the organization. Talent Management as a core function of Human Resource Management has limitless potential implications for practicing HR professionals or the policy makers to effectively create systems and processes which promotes Talent Culture and adopt best Talent Management practices as a strategic tool in the global Talent War. The present paper seeks to provide a smart peep into a wide spectrum of new concepts of Talent and Talent Management Practices in alignment with the new business demands of present times and explore how seamlessly Talent is being integrated in the organizational strategy.